LEGAL ANALYSIS OF ALLEGED HUMAN RIGHTS VIOLATIONS IN THE ENTERTAINMENT INDUSTRY: A CASE STUDY OF THE ORIENTAL CIRCUS IN INDONESIA - Aufa, Muhamad Gagah; Ramadhani, Aura Nafisha; Siregar, Andita Resia Raymond (Zhata Institut, 2025)
The case of Oriental Circus Indonesia (OCI) involves allegations of systematic physical violence, exploitation, and modern slavery against performers that have remained legally unresolved for twenty-eight years. This research is paramount due to the absence of systematic academic inquiry into OCI’s human rights violations and the necessity to address systemic failures in protecting vulnerable groups within the entertainment industry. This study employs a library research method using juridical-normative and critical-sociological approaches to analyze secondary legal data and digital evidence. The analysis reveals that the reported practices constitute gross human rights violations and modern slavery, fundamentally breaching the 1945 Constitution, Law Number 39 of 1999, and international conventions such as the Convention on the Rights of the Child. Furthermore, the study concludes that structural barriers and political constraints hinder access to justice, necessitating the formation of an independent Joint Fact Finding Team to ensure legal accountability and comprehensive victim rehabilitation.